Optimum signal in a diffusion leaky integrate-and-fire neuronal model - Lánský, Petr; Sacerdote, Laura; Zucca, Cristina (Mathematical biosciences, 2007)
An optimum signal in the Ornstein-Uhlenbeck neuronal model is determined on the basis of interspike interval data. Two criteria are proposed for this purpose. The first, the classical one, is based on searching for maxima of the slope of the frequency transfer function. The second one uses maximum of the Fisher information, which is, under certain conditions, the inverse variance of the best possible estimator. The Fisher information is further normalized with respect to the time required to make the observation on which the signal estimation is performed. Three variants of the model are investigated. Beside the basic one, we use the version obtained by inclusion of the refractory period. Finally, we investigate such a version of the model in which signal and the input parameter of the model are in a nonlinear relationship. The results show that despite qualitative similarity between the criteria, there is substantial quantitative difference. As a common feature, we found that in the Ornstein-Uhlenbeck model with increasing noise the optimum signal decreases and the coding range gets broader.
Keywords: financování organizované; Animals; Refractory Period, Electrophysiological; membránové potenciály; Action Potentials; Models, Neurological; modely neurologické; lidé; Neural Conduction; neurony; refrakterní doba elektrofyziologická; Algorithms; nervové vedení; Stochastic Processes; Financing, Organized; Neurons; algoritmy; stochastické procesy; zvířata; akční potenciály; Membrane Potentials; Humans